DRE!: A RULE-BASED SOFTWARE REQUIREMENT EXTRACTION FRAMEWORK FOR INDONESIAN DOCUMENTS - Maulana, Moh. Zulfiqar Naufal; Adrian, Ahmad Reza; Adhyaksa, Fathan Alfariel; Prasetya, Didik Dwi; Ardiansyah, Jevri Tri; Adha, Hanif Rifai (STKIP PGRI Tulungagung, 2026)
Extracting software requirements from descriptive documents is a crucial yet challenging phase in software engineering, par-ticularly when performed manually. This research proposes DRE!, a framework for automatically extracting functional requirements from Indonesian-language system descriptions. The employed methodology applies a concise workflow that begins with data acquisition, involving a system description and a predefined list of actors. The process continues with preprocessing, word dependency parsing for grammatical analysis, actor detection featuring a previous-sentence refer-ence mechanism, and requirement construction using an ac-tor-centric template. The workflow concludes with a similarity check (cosine similarity) for redundancy elimination. The framework was evaluated on eight software description da-tasets. The evaluation results demonstrate promising perfor-mance, with F1-Scores on seven of the eight datasets ranging from 0.76 to 0.88. Peak performance was recorded on the